Female Executives and Leverage of Public Companies in Indonesia : Does Age Matter? - Christie, Florencia; Hermanto, Florentina Elena; Kosasih, Valerie Angela; Chandera, Yane; Suthiono, Henry (Universitas Prasetiya Mulya, 2025)
The study aims to examine the effect of the proportion of women in the board of directors on the debt level of publicly listed companies in Indonesia, as measured by the debt-equity ratio (DER). Additionally, this research seeks to determine whether the age of female directors strengthens or weakens the established relationship between female directors and company DER. The study employs a multiple regression method with a sample of 64 publicly listed companies on the Indonesian Stock Exchange during the years 2019-2023. Findings reveal that the presence of women on the board of directors has a significant negative relationship with company DER, indicating that a higher number of female directors may decrease company DER. Furthermore, findings also show that age strengthens the aforementioned negative relationship, although with a lower significance level of 10%. Thus concluding that female and senior directors reduce a company’s tendency to take on debt, due to their risk averse nature.